Why Use of Interventions Targeting Outdoor Biting Mosquitoes will be Necessary to Achieve Malaria Elimination - Govella, Nicodem J.; Ferguson, Heather (Frontiers in Physiology, 2012)
By definition, elimination of malaria means permanent reduction to zero of locally incidence of infections. Achieving this goal among other reasons, it requires fully understanding on where and when persons are most exposed to malaria vectors as these are fundamental for targeting interventions to achieve maximum impact. While elimination can be possible in some settings with low malaria transmission intensity and dominated with late and indoor biting of vectors using Long Lasting Insecticidal Nets (LLIN) and Indoor Residual Spraying (IRs), it’s difficult and even impossible in areas with high and where majority of human exposure to transmission occurs outside human dwellings. Recently in response to wide spread use of LLIN and IRS, human risk of exposure to transmission is increasingly spread across the entire night so that much of it occurs outdoors and before bed time. This modification of vector populations and behaviour has now been reported from across Africa, Asia and from the Solomon Islands. Historical evidence shows that even in areas with intervention coverage exceeding 90% of human population it was so hard to even push prevalence down below the pre elimination threshold of 1% being compromised mainly with the outdoor residual transmission. Malaria control experts must however continue to deliver interventions that tackle indoor transmission but considerable amount of resources that target mosquitoes outside of houses and outside of sleeping hours will therefore be required to sustain and go beyond existing levels of malaria control and achieve elimination.